PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN (SAP) BERBASIS AKRUAL, PEMANFAATAN TEKNOLOGI INFORMASI, DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING (STUDI EMPIRIS PADA PEMERINTAHAN KABUPATEN KAMPAR) - Ningrum, Anggreini; Hardi, Hardi; Al, L Azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This research was conducted at the Kampar District Government in RiauProvince . The purpose of this study is to analyze The Effect of Aplication ofGovernment Accounting Standards (SAP) based on Accrual, Utilization ofInformation Technology, and Competence of Human Resources on The Quality ofFinancial Reports with Organizational Commitment as a Moderating Variable .The population and sample in this study were all SKPDs of the Kampar DistrictGovernment in Riau Province which acted as heads of work units or structuralofficials in the Village Work Unit (SKPD) represented by the Head of Finance,Treasurer and Chief of Staff of Government Institution Programs. The populationand sample in this study were 87 peoples. This study uses the ModeratedRegression Analysis (MRA) with the regression equation. These results prove thatthe application of accrual-based government accounting standards, utilization ofinformation technology, components of human resources, application ofgovernment accounting standards, utilization of information technology andcompetence of human resources affect the quality of financial reports in theKampar Government, and Organizational Commitment as a Moderating Variableaffect Aplication of Government Accounting Standards (SAP) based on Accrual,Utilization of Information Technology, and Competence of Human Resources onThe Quality of Financial ReportsKeywords : Government Accounting Standards (SAP), Utilization of InformationTechnology, Competence of Human Resources, Quality of FinancialReport,Organizational Commitment